Better corporate governance and risk in dual banking environment : evidence from Malaysia. - Htay, Sheila Nu Nu; Adnan, Muhammad Akhyar; Ab. Rashid, Hafiz Majdi; Mydin Meera, Ahamed Kameel (IIUM Press, 2011)
The objective of this paper is to examine the impact of corporate governance on the risk of banks. A sample of twelve listed bank holding companies is examined over a ten year period (1996-2005). All the sample banks are offering Islamic banking products, in addition to conventional products. Based on the panel data analysis, separate board leadership structure, higher proportion of independent directors, smaller board size, lower director ownership, higher institutional ownership and higher block ownership seem to have lower risk. The study applies the agency theory. All findings except director ownership are in line with theoretical expectation. It might be due to three main reasons as discussed in the paper